The microbiota and radiotherapy for head and neck cancer: What should clinical oncologists know?. (September 2022) - Reis Ferreira, Miguel; Pasto, Anna; Ng, Tony; Patel, Vinod; Guerrero Urbano, Teresa; Sears, Cynthia; Wade, William G.
Highlights: Radiotherapy is a linchpin in head and neck squamous cell carcinoma treatment. The microbiota may modulate radiotherapy outcomes. The oral microbiota may contribute to head and neck cancer development. The microbiota may contribute to radiotherapy toxicity and efficacy. Abstract: Radiotherapy is a linchpin in head and neck squamous cell carcinoma (HN-SCC) treatment. Modulating tumour and/or normal tissue biology offers opportunities to further develop HN-SCC radiotherapy. The microbiota, which can exhibit homeostatic properties and be a modulator of immunity, has recently received considerable interest from the Oncology community. Microbiota research in head and neck oncology has also flourished. However, available data are difficult to interpret for clinical and radiation oncologists. In this review, we focus on how microbiota research can contribute to the improvement of radiotherapy for HN-SCC, focusing on how current and future research can be translated back to the clinic. We include in-depth discussions about the microbiota, its multiple habitats and relevance to human physiology, mechanistic interactions with HN-SCC, available evidence on microbiota and HNC oncogenesis, efficacy and toxicity of treatment. We discuss clinically-relevant areas such as the role of the microbiota as a predictive and prognostic biomarker, as well as the potential of leveraging the microbiota and its interactions with immunity to improve treatment results. Importantly, we draw parallels with other cancers where research is more mature. We map out future directions of research and explain clinical implications in detail.